KIR2DL4/HLA‐G polymorphisms were associated with HCV infection susceptibility among Chinese high‐risk population. Issue 3 (15th March 2023) - Feng, Zepei; Huang, Peng; Zhang, Jinwei; Xia, Xueshan; Zhang, A‐mei; Zeng, Tian; Chen, Qiong; Zhu, Chuanlong; Tan, Weilong; Zhang, Yun; Yue, Ming
Abstract: Killer‐cell immunoglobulin‐like receptors 2DL4 ( KIR2DL4 ) and the human leukocyte antigen class I‐G ( HLA‐G ) display vital parts in immune responses against hepatitis C virus (HCV) infection. We select four potentially functional single nucleotide polymorphisms (SNPs) of KIR/HLA to explore the associations between KIR2DL4/HLA‐G genetic variants and HCV infection results. In the present case‐control study, a total of 2225 HCV‐infected high‐risk subjects, including 1778 paid blood donors (PBD) and 447 drug users were consecutively recruited before treatment from 2011 to 2018. KIR2DL4 ‐rs660773, KIR2DL4 ‐rs660437, HLA‐G ‐rs9380142, and HLA‐G ‐rs1707 SNPs were sorted as genotypes in the subdivided groups, involving 1095 uninfected controls subjects, 432 spontaneous HCV clearance subjects and 698 HCV persistent infection subjects. After genotyping experiments using the TaqMan‐MGB assay, modified logistic regression was used to calculate the correlation among the SNPs and HCV infection. The SNPs were functionally annotated using bioinformatics analysis. Following adjusting by age, sex, alanine aminotransferase, aspartate aminotransferase, IFNL3 ‐rs12979860, IFNL3 ‐rs8099917, and the infection route, the logistic regression analysis discovered that KIR2DL4 ‐rs660773 and HLA‐G ‐rs9380142 were correlated with vulnerability to HCV infection (all p  < 0.05). In a locus‐dosage way, compared with subjects carrying the rs9380142‐AA or rs660773‐AA genotypes, subjects with rs9380142‐AG or rs660773‐AG/GG (all p  < 0.05) were more vulnerable to HCV infection; the overall impact of their risk genotypes (rs9380142‐AGrs660773‐AG/GG) was correlated with an elevated incidence of HCV infection ( p trend  < 0.001). In the Haplotype analysis, patients with haplotype AG were more likely to contract HCV compared to those with the highest common AA haplotype ( p  = 0.002) were higher in susceptibility to infect HCV. The SNPinfo web server estimated that rs660773 is a transcription factor binding site, whereas rs9380142 is a potential microRNA‐binding site. In two Chinese high‐risk population (PBD and drug uesrs), KIR2DL4 rs660773‐G and HLA‐G rs9380142‐G alleles polymorphisms are related to HCV susceptibility. KIR2DL4 / HLA‐G pathway genes might affect the innate immune responses by regulating KIR2DL4/HLA‐G transcription and translation play a potential role in HCV infection.